Features of transport and communications infrastructure in rural area of Donetsk region - Нємець, Л. М.; Сегіда, К. Ю.; Яковлева, Ю. К. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2014)
This article analyzes the characteristics of transport and communication infrastructure in rural area of Donetsk region. Social infrastructure components in the rural area have been shown. The place of the transport and communication components in the social infrastructure has been given. Temporal and spatial features of the transport complex functioning by types were considered. Railway transport in rural areas is developed near large and medium size cities due to the development of industry in the region. The vast proportion of the rural population uses the roads (motor transport). Dynamics of passengers’ transportation by road has increased significantly over the last 5 years. In rural areas, accessibility is not uniform, it depends on the remoteness of the towns, highways and railway junctions. The features of transport access for rural areas of Donetsk region were shown. The features of communication in rural areas were given. The communication means in Donetsk region include telegraph, fax, telex, modem, speaker spotlight at sea, radio, mobile phone and Internet. The level of transport and communication infrastructure functioning, especially in rural areas, is an important indicator of social development. The features, factors, problems of transport and communication infrastructure of the Donetsk region has been investigated, which allows us to offer ways to optimize the social needs of the rural population.